2009
DOI: 10.1177/0310057x0903700101
|View full text |Cite
|
Sign up to set email alerts
|

Dose Requirements for Propofol Anaesthesia for Dental Treatment for Autistic Patients Compared with Intellectually Impaired Patients

Abstract: We had clinical grounds to suspect that patients with autism had greater propofol requirements during dental procedures than patients with intellectual impairment without autism. This hypothesis was tested by an audit of a standard anaesthetic technique. The audit was approved by our Hospital Ethics Committee. We compared the propofol requirements and effect using a standardised protocol during dental treatment in 56 autistic patients (age range three to 35 years) and 56 intellectually impaired patients (age r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The patients in the ASD group might also have a lowered pain threshold for some qualities of pain. During dental treatment under general anaesthesia the need of anaesthetic medication (the propofol requirement) was found to be greater amongst patients with autism than intellectually impaired controls [25]. …”
Section: Discussionmentioning
confidence: 99%
“…The patients in the ASD group might also have a lowered pain threshold for some qualities of pain. During dental treatment under general anaesthesia the need of anaesthetic medication (the propofol requirement) was found to be greater amongst patients with autism than intellectually impaired controls [25]. …”
Section: Discussionmentioning
confidence: 99%
“…7,41–43 A study by Asahi et al 42 showed that for dental procedures, autistic patients have greater requirements for propofol, an intravenous anesthetic, than do intellectually impaired patients. However, the mechanisms of action of propofol and inhalational anesthetics are substantially different.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the aforementioned changes may lead to drug resistance and EEG changes. This possibility is supported by the finding that patients who present with autism spectrum disorder as a result of deficient neural development have greater propofol requirements for anesthesia during ordinary dental treatment compared with intellectually impaired patients [15]. …”
Section: Discussionmentioning
confidence: 99%